2010
DOI: 10.1074/jbc.m109.096479
|View full text |Cite
|
Sign up to set email alerts
|

Versican Facilitates Chondrocyte Differentiation and Regulates Joint Morphogenesis

Abstract: . These results suggest that versican facilitates chondrogenesis and joint morphogenesis, by localizing TGF-␤ in the extracellular matrix and regulating its signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 44 publications
1
85
0
Order By: Relevance
“…35 In addition, we previously reported that Vcan regulates local concentrations of TGFb. 19 TGFb was strongly immunostained in the outer region of the QRsP11/Vcan Cre tumor masses and moderately on the inside, whereas there was little immunostaining in the tumor masses from QRsP11/Vcan GFP mice (Fig. 3a, TGFb).…”
Section: Absence Of Versican Upregulates Ha-and Tgfb-mediated Signal mentioning
confidence: 97%
See 2 more Smart Citations
“…35 In addition, we previously reported that Vcan regulates local concentrations of TGFb. 19 TGFb was strongly immunostained in the outer region of the QRsP11/Vcan Cre tumor masses and moderately on the inside, whereas there was little immunostaining in the tumor masses from QRsP11/Vcan GFP mice (Fig. 3a, TGFb).…”
Section: Absence Of Versican Upregulates Ha-and Tgfb-mediated Signal mentioning
confidence: 97%
“…X-gal staining was performed as previously described. 19 Images were obtained using an Olympus BX50 microscope and Olympus DP71 digital camera.…”
Section: Molecular Cancer Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…42 Conditional knockout of versican has demonstrated its importance both during chondrogenesis and in binding the profibrotic cytokine TGF-β. 43 Versican is a major component of the early fibroproliferative matrix in lung fibrosis where its deposition is associated with fibroblast migration and proliferation, preceding collagen deposition. [44][45][46] It is also associated with the neointima in atherosclerosis and restenosis.…”
mentioning
confidence: 99%
“…Thus, the negative charge in various positions along the GAG chains is due to the sugar acid residues and/or sulfate groups (Prydz and Dalen, 2000). GAGs have been known to play many roles in both physiological and pathological conditions or diseases, including signaling activity during chondrocyte differentiation (Choocheep et al, 2010), angiogenesis, anti-coagulation, axonal growth, wound healing, pulmonary and vascular diseases, and tumor progression (Gandhi and Mancera, 2008). Additionally, chondroitin sulfate and hyaluronic acid have been reported to suppress cartilage degradation for the treatment of osteoarthritis (Monfort et al, 2005).…”
Section: Introductionmentioning
confidence: 99%